1985
DOI: 10.1016/s0735-1097(85)80260-6
|View full text |Cite
|
Sign up to set email alerts
|

Relation between left ventricular global and regional function and extent of myocardial ischemia in the canine heart

Abstract: To develop a quantitative relation between the overall severity of acute ischemia and left ventricular global and regional function, two minor axis internal diameters and myocardial wall thickness were determined using ultrasonic crystals in 10 open chest dogs with carotid-left anterior descending artery cannulation. The overall extent of ischemia produced by graded stenosis of the cannulation system was estimated by total myocardial blood flow deficit, calculated using radioactive microspheres and a balloon-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 30 publications
1
10
1
Order By: Relevance
“…These results seem to differ from those of the previous reports (Akaishi et al 1985;Noma et al 1988a, b;Ishikawa et al 1993;Sakuma et al 1993) which showed that the increase of the isovolumetric shortening in the non-ischemic region reflected the increase of the isovolumetric bulging in the ischemic region, both in the preload change and in the afterload change. The changes of the end-diastolic relations between the non-ischemic and ischemic regions partly affected the relationship between these two regions in the isovolumetric phase.…”
Section: Regional Wall Motion In the Isovolumetric Phasecontrasting
confidence: 96%
See 1 more Smart Citation
“…These results seem to differ from those of the previous reports (Akaishi et al 1985;Noma et al 1988a, b;Ishikawa et al 1993;Sakuma et al 1993) which showed that the increase of the isovolumetric shortening in the non-ischemic region reflected the increase of the isovolumetric bulging in the ischemic region, both in the preload change and in the afterload change. The changes of the end-diastolic relations between the non-ischemic and ischemic regions partly affected the relationship between these two regions in the isovolumetric phase.…”
Section: Regional Wall Motion In the Isovolumetric Phasecontrasting
confidence: 96%
“…In regional ischemic heart, the effects of changes in preload, afterload and contractile state on regional wall motion have been reported (Akaishi et al 1985;Lew and Ban-Hayashi 1985;Noma et al 1988a, b;Ishikawa et al 1993;Sakuma et al 1993). It has been shown that the degree of isovolumetric shortening in the non-ischemic region reflects the degree of paradoxical systolic expansion in the ischemic myocardium.…”
mentioning
confidence: 99%
“…It is well recognized that regional ischemia results in local contractile dysfunction [5,6], which may or may not be reflected in a loss of global contractile function [24,25], The loss of local function while retaining global func tion has been reported by several investiga tors [5,6], In the present study, local function 40 Yokoyama/Novitzky/Deal/Snow T < and the Stunned Myocardium remained depressed despite recovery of global function, as measured by conventional pa rameters. e.g.…”
Section: Discussionsupporting
confidence: 49%
“…As seen from the tracing of ischemic segment length during coronary occlusion, the motion of the acutely ischemic myocardium was characterized by lenthening (bulging) in early systole, slowly decreasing length in mid-systole, rapidly decreasing length (recoil) in early diastole, and slowly increasing length in the remainder of diastole. In the nonischemic zone, the EDL increased and showed increased shortening (Akaishi et al, 1985b), and chamber diameter showed increased end-diastolic dimension and decreased shortening (Akaishi et al, 1985a) after coronary occlusion. With blood with- Abbreviations: Subendo = subendocardial blood flow (ml/min per g); Subepi • flow (ml/min per g); Mid = mid-myocardial blood flow (ml/min per g).…”
Section: Myocardial Blood Flow (Table 2)mentioning
confidence: 99%
“…One crystal pair at each site was implanted subendocardially in a circumferential plane for measurement of segment length (Weintraub et al, 1981). In three dogs, a pair of ultrasonic crystals was implanted on the anterior and posterior endocardial surfaces through an incision in the LV apex to measure the LV anteriorposterior minor axis internal diameter, as described previously (Akaishi et al, 1985a). Pacing electrodes were sutured to the left atrial appendage.…”
mentioning
confidence: 99%